Rare earth ion Tb(3+) doped natural sodium feldspar (NaAlSi(3)O(8)) Luminescent properties and energy transfer - Halmurat, Dilare (Sci Rep, 2019)
In this study, Tb(3+)—doped natural sodium feldspar (NaAlSi(3)O(8)) phosphors have been successfully prepared using high−temperature solid—state method with natural sodium feldspar as a substrate. Energy—dispersive X—ray spectrometry analysis (EDX) of NaAlSi(3)O(8) showed that 0.03 wt% of Eu element was present, and elemental distribution mapping analysis showed that the distribution of trace Eu in minerals was aggregated. The crystal structure and luminescence properties of the natural sodium Eu—containing feldspar and synthetic sodium feldspar NaAlSi(3)O(8):Eu(3+), Tb(3+) phosphors are discussed in detail. The crystal structure analysis of the samples showed that the Na(+) in the natural matrix was partly replaced by the doped Tb(3+). Studies on the photoluminescence properties of the samples indicate that Eu does not form a luminescent center in the natural mineral, however, the strong characteristic peak of Eu(3+) at 615 nm appears after doping with Tb(3+) and the peak at 615 nm increases with the increase of Tb(3+) concentration. According to the above spectral results, the energy transfer from Tb(3+) to Eu(3+) is obtained. Through the measurement and analysis of color coordinates, it is found that with the increase of Tb(3+) concentration, the luminescence color of the samples can be regulated in the green to red region. NaAlSi(3)O(8):Eu(3+) Tb(3+) phosphors has potential application value.